The role of mobile ICT in repair worker communities of practice - Chris Ivory; Rebecca Casey; Kayleigh Watson (International Telecommunications Society (ITS), 2016)
The article addresses the lack of focus, in the literature on work and communications technology, on the role played by communities of practice (CoPs) in mediating the impacts of technology change on work. It is argued that the particular characteristics of CoPs, the fact that they are regarded as an end in themselves by community members, make them a key part of the technology-organisation dialectic. By examining the role played by CoPs, it is possible to gain a better understanding of the relationship between work and technology - in particular the unintended consequences of technology change for work and, indeed, for CoPs themselves.
Keywords: 330; Communications; Technology; Change; Communities of Practice; Repair Workers